Comparison of Capsular Tension Ring Implantation before vs. after Toric Intraocular Lens for Rotational Stability - Cetinkaya, Servet; Ucar, Fikret (Klinische Monatsblätter für Augenheilkunde, 2023)
Purpose To compare the effect of implanting the capsular tension ring (CTR) before or after a toric intraocular lens (IOL) on rotational stability in patients with cataract and astigmatism.Methods This is a randomized retrospective study. Patients who underwent phacoemulsification combined with toric IOL implantation due to cataract and astigmatism between February 2018 and October 2019 were enrolled in the study. Group 1 consisted of 53 eyes of 53 patients in whom the CTR was placed into the capsular bag after the implantation of the toric IOL. On the other hand, group 2 consisted of 55 eyes of 55 patients in whom the CTR was placed into the capsular bag before implantation of the toric IOL. The two groups were compared in terms of preoperative and postoperative astigmatism, uncorrected visual acuity (UCVA), best-corrected visual acuity (BCVA), and postoperative IOL rotation degree.Results There were no significant differences between the two groups related to age and sex (p > 0.05) or the mean preoperative spherical value, UCVA, BCVA, and corneal astigmatism (p > 0.05). Although the mean postoperative residual astigmatism of the first group (− 0.29 ± 0.26) was lower than that of the second (− 0.43 ± 0.31), the difference was not statistically significant (p = 0.16). The mean degree of rotation was 0.75 ± 2.66° in group 1 and 2.90 ± 6.57° in group 2, which was found to be statistically significant (p = 0.02).Conclusion The implantation of CTR after a toric IOL provides further rotational stability and more effective astigmatic correction.
Keywords: CTR; toric IOL; cataract; astigmatism; postoperative rotation